Phytochemical, Total Phenolic, and Antioxidant Activity of Ginger Extract and Its Use in the Synthesis of Eco-friendly Silver Nanoparticles - Abdulkadir Mohammed Noori Jassim; Maryam Abdulghafor Ahmed; Salam A. H. Al-Ameri; Safana Ahmed Farhan; Omar M. Noori (Iraqi Journal of Industrial Research)
The Ginger (Zingiber Officinale) extract contain a lot of constituents and elements. Ginger extract can effort as a good bio-reductant to produce silver nanoparticles (AgNPs). The AgNPs Green synthesis was achieved by using the Ginger plant extract with AgNO3. The green synthesis of AgNPs is the best developing procedure for preparation, since this process is easier than other procedures, eco-friendly and fewer times consuming. The produced AgNPs were characterizing via UV-Vis, FTIR, AFM, SEM, Zeta potential and EDX. The optimal conditions for the synthesis AgNPs which was confirmed through UV–Vis spectrophotometer. Also, the AgNPs has been characterized by AFM with average size of 53.45 nm, SEM with average size of 21.91 to 33.79 nm. Antioxidant and free radical scavenge activity are examined through TLC and DPPH test, the results shows that the Ginger have a high activity, moreover, this activity increased with characterized AgNPs.